PENGELOLAAN ARSIP DINAMIS AKTIF DI DEPARTEMENT INTERNAL WAREHOUSE PT. SARI HUSADA UNIT I YOGYAKARTA - LESTARI, SRI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final assignment report explain about managing active record in Departement Internal Warehouse. The important thing about managing active record are how the condition of archives in there, both incoming and outgoing mail. Mail handling includes creating archives, tool and infrastructure of archives, safety system of archives, and discovered archives. This final assignment report is supported by three methods, observation, interview and literature study. Observation methods through direct practice in PT. Sari Husada. The second method, interview, through asking people who know well about the history of PT. Sari Husada. The last methods is data collection about managing active record. The conclusion from result of observation in PT. Sari Husada show that comprehensive tools in PT. Sari Husada can make easier for archives storage. The safety system in PT. Sari Husada work efficient and effective so that the archives easy to be found.